Synthesis of 4-aminoquinoline analogues and their platinum(II) complexes as new antileishmanial and antitubercular agents - Carmo, Arturene M. L.; Silva, Flavia M. C.; Machado, Patricia A.; Fontes, Ana P. S.; Pavan, Fernando Rogério [UNESP]; Leite, Clarice Queico Fujimura [UNESP]; Leite, Sergio R. de A. [UNESP]; Coimbra, Elaine S.; Da Silva, Adilson D. (Elsevier France-editions Scientifiques Medicales Elsevier, 2011)
A series of 4-amino-7-chloroquinoline derivatives were synthesized by the reaction of 4,7-dichloroquinoline with the corresponding diamine and then with propargyl bromide. In addition, platinum(II) complexes were obtained by reacting some of the organic derivatives with K(2)PtCl(4). Several of the synthesized compounds displayed antituberculosis activities. Compound 3 was 47.5 times more active than amphotericin B against Leishmania chagasi (IC(50) = 0.04 mu g/mL). Compounds 5, 6, 7, 9, 10, 11 and 13 presented promising results against Mycobacterium tuberculosis, with MIC values ranging from 12.5 to 15.6 mu g/mL, comparable to the "first and second line'' drugs used to treat tuberculosis. (C) 2011 Elsevier Masson SAS. All rights reserved.
Keywords: 4-aminoquinoline analogues; Platinum(II) complexes; Antileishmanial; Antitubercular; Leishmania; Mycobacterium tuberculosis